Hereditary disorders of bulls imported semen to turkey in 2015 - Şeref İnal; Mustafa Çam (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was aimed to detect hereditary defects of bulls that imported their frozen semen to Turkey in 2015. Materials and Methods: As the source of knowledge, the websites of various companies that produce frozen semen, AI bull catalogs, and databases of bull semen companies have been used. Results: The result of the research revealed that 1.334.827 of 4.566.553 semen had at least one genetic defects (29.23%). In accordance with the procedures and principles with regard to the import of “sperm, ovum and embryo” issued by the Ministry, the sperms with haplotypes, which are banned legally from entering the country, have been found out. At least 14% of bull semen had A1 beta-casein gene which threatens human health. It had no got sufficient information about the genetic structure of nearly half of the bulls. Conclusion: It may be stated that authorities should review and update the list of genetic defects especially seen in Simmental breed bulls stated in binding guidelines concerning procedures and principles.